Water Quality Assessment of Tigris River Using Multivariate Statistical Techniques - Alharbawee , Noor A.H.; Mohammed, Ahmed Jasim (Iraqi Journal of Science, 2024)
Factor and cluster analysis, two multivariate statistical approaches, have been used to analyze temporal and spatial variations and pollutants sources effecting the water quality of Tigris River from the north to the south of Baghdad city. From October 2021 to September 2022, 15 water quality parameters (electrical conductivity (EC), pH, water temperature (WT), turbidity (Tur), total hardness (TH), biochemical Ooxygen Ddemand (BOD), dissolved oxygen (DO), Mg+, Ca+, SO4, dissolved solids (TDS), total suspended solids (TSS), total chlorine (TC), Cr, and Al) were tested at five monitoring sites (Balad, Al-Ghrai’at, Al-Shuhada'a Bridge, Al-Za’franiya, and Jisr Diyala), along the study area of the river. Results revealed that the major factor that affects the water quality in the study area is the anthropogenic factor. Spatial cluster analysis of the monitoring sites revealed three different groups that were compared to one another where each site suggested a different degree of contamination in the Tigris river water quality.